Engineering Cancer/Testis Antigens With Reversible S-Cationization to Evaluate Antigen Spreading - Miyamoto, Ai; Honjo, Tomoko; Masui, Mirei; Kinoshita, Rie; Kumon, Hiromi; Kakimi, Kazuhiro; Futami, Junichiro (Frontiers in Oncology, 2022)
Serum autoantibody to cancer/testis antigens (CTAs) is a critical biomarker that reflects the antitumor immune response. Quantitative and multiplexed anti-CTA detection arrays can assess the immune status in tumors and monitor therapy-induced antitumor immune reactions. Most full-length recombinant CTA proteins tend to aggregate. Cysteine residue-specific S-cationization techniques facilitate the preparation of water-soluble and full-length CTAs. Combined with Luminex technology, we designed a multiple S-cationized antigen-immobilized bead array (MUSCAT) assay system to evaluate multiple serum antibodies to CTAs. Reducible S-alkyl-disulfide-cationized antigens in cytosolic conditions were employed to develop rabbit polyclonal antibodies as positive controls. These control antibodies sensitively detected immobilized antigens on beads and endogenous antigens in human lung cancer-derived cell lines. Rabbit polyclonal antibodies successfully confirmed the dynamic ranges and quantitative MUSCAT assay results. An immune monitoring study was conducted using the serum samples on an adenovirus‑mediated REIC/Dkk‑3 gene therapy clinical trial that showed a successful clinical response in metastatic castration-resistant prostate cancer. Autoantibody responses were closely related to clinical outcomes. Notably, upregulation of anti-CTA responses was monitored before tumor regression. Thus, quantitative monitoring of anti-CTA antibody biomarkers can be used to evaluate the cancer-immunity cycle. A quality-certified serum autoantibody monitoring system is a powerful tool for developing and evaluating cancer immunotherapy.